Probiotics Partly Suppress the Impact of Sugar Stress on the Oral Microbiota—A Randomized, Double-Blinded, Placebo-Controlled Trial - Lundtorp Olsen C; Massarenti L; Vendius VFD; Gürsoy UK; Van Splunter A; Bikker FJ; Gürsoy M; Damgaard C; Markvart M; Belstrøm D (Switzerland, 2025)
The aim was to test if probiotics counteract oral dysbiosis during 14 days of sugar stress and subsequently help restore oral homeostasis. Eighty healthy individuals received either probiotics (n = 40) or placebo lozenges (n = 40) for 28 days and rinsed with a 10% sucrose solution 6-8 times during the initial 14 days of the trial. Saliva and supragingival samples were collected at baseline, day 14, and day 28. Saliva samples were analyzed for levels of pro-inflammatory cytokines, albumin, and salivary enzyme activity. The supragingival microbiota was characterized according to the Human Oral Microbiome Database. After 14 days of sugar stress, the relative abundance of Porphyromonas species was significantly higher (p = 0.03) and remained significantly elevated at day 28 in the probiotic group compared to the placebo group (p = 0.004). At day 28, the relative abundance of Kingella species was significantly higher in the probiotic group (p = 0.03). Streptococcus gordinii and Neisseria elongata were associated with the probiotic group on day 28, while Streptococcus sobrinus was associated with the placebo group on day 14 and day 28. On day 28, the salivary albumin level was significantly lower in the probiotic group. The present study demonstrates a potential stabilizing effect on the supragingival microbiota mediated by consumption of probiotics during short-term sugar stress.